An Efficient Scheme To Improve The Overlapped Transmission In Wireless Adhoc Network Using Carrier Sense Multiple Access (International Journal of Engineering and Computer Science, 2013)
— Wireless network refers to any type of computer network that is not connected by cables of any kind. Wireless network is divided into multiple types such as Wireless LAN, Wireless MAN, Cellular networks and Ad-hoc networks etc. In wireless ad-hoc networks, interference is one of the major impairments that reduce the performance of a network. To reduce this interference, we have been using a technique called Interference Cancellation(IC). Instead of this Interference Cancellation some of the techniques such as Multi User Detection (MUD), Multi Packet Reception (MPR) has been used in networks. However MPR is typically requires a very complicated hardware. As well as it is not suitable without knowing a interfering signals. Therefore we moved to Overlapped Transmission technique. In this overlapped transmission technique, a multiple transmission can occur in the same network. These techniques have much lower signal processing demand than the Multi Packet Reception. Overlapped Carrier Sense Multiple Access (OCSMA) protocol can be used to improve the performance of overlapped transmission technique. We develop a MAC protocol based on the IEEE 802.11 standard to support the overlapped transmission in networks. And we investigate the impact of overlapped transmission on the performance of Transmission Control Protocol in wireless ad-hoc MIMO networks using directional antennas.